Integrating Psychology, Religion, and Culture: The Promise of Qualitative Inquiry - Pak, Jenny Hyun Chung (Brill research perspectives in religion and psychology, 2020)
Although science was originally broadly conceptualized as a systematic, rigorous activity to produce trustworthy knowledge, psychologists, those following the mainstream, adopted a single philosophy of science and strictly enforced natural science as the only proper “scientific” psychology. Qualitative research has been part of modern psychology from the beginning, but it was obscured for nearly a century as positivist epistemology came to dominate the field. Building culturally robust and intelligible theories capable of responding more effectively to complex problems faced by a rapidly changing world calls for openness in methodological diversity. Deeply rooted in a hermeneutic tradition, cultural psychology has challenged the appropriateness of seeking reductive knowledge because higher mental processes such as religious beliefs, values, and choices are bound by historical and cultural context. As greater interdisciplinary integration and methodological innovations are necessary to keep psychology of religion relevant, narrative inquiry has emerged as a promising integrative paradigm.